5a+7=19+3a

Simple and best practice solution for 5a+7=19+3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+7=19+3a equation:


Simplifying
5a + 7 = 19 + 3a

Reorder the terms:
7 + 5a = 19 + 3a

Solving
7 + 5a = 19 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
7 + 5a + -3a = 19 + 3a + -3a

Combine like terms: 5a + -3a = 2a
7 + 2a = 19 + 3a + -3a

Combine like terms: 3a + -3a = 0
7 + 2a = 19 + 0
7 + 2a = 19

Add '-7' to each side of the equation.
7 + -7 + 2a = 19 + -7

Combine like terms: 7 + -7 = 0
0 + 2a = 19 + -7
2a = 19 + -7

Combine like terms: 19 + -7 = 12
2a = 12

Divide each side by '2'.
a = 6

Simplifying
a = 6

See similar equations:

| 4x+3=-5x-14 | | -7c=-11.7c-4.7 | | 7c+c=304 | | 8.7v-3.03+11.8v=19.5v-10.83 | | -1=b+8 | | 6z-30=0 | | x^6+3x^5-18x^4=0 | | 14x+7=5x-6x | | x-0.25x=24.00 | | -8=8+4u | | -18=4v-6v | | 3x=y(x+y+19) | | 5(v-9)-1=-7(3v+7)-v | | 11=3(v-3)-7v | | (A+6)+((A+2)+6)=(3A)+6 | | -13=3x-7 | | 2.1x+45.2+3.2-8.4x= | | 6x+12y=20 | | 14x*7=5x-6x | | -8x+4(x+6)=20 | | 5(4n-8)=-28+8n | | -3(r+4)=-41 | | k+4-7=3 | | 2.1x+45.2+3.2-824x= | | -16w+7.38=-16.7w+2.97 | | 7y+49=9(y+7) | | 7r-6r=5 | | 20=10v-5v | | 6=-6u+4(u+4) | | 6m-2=32 | | 0.3x=0.09 | | 6(x+3)=3(8+4x)-6 |

Equations solver categories